Factors influencing glycaemic control in diabetics at three community health centres in Johannesburg - Timothy, Geraldine Antoinette (My University, 2011)
Introduction: The complications associated with diabetes usually occur over a long period of time and are mainly influenced by poor glycaemic control. Diabetic complications impact on the individual, the healthcare delivery system, and also have high cost implications. A number of studies have shown the management of diabetes to be sub-optimal in primary health care settings. Barriers that impair a patients’ ability to achieve good glycaemic control can be looked at from a patient, health facility and health professional perspectives. Good glycaemic control will not only benefit the individual patient but will also have a positive financial impact on South Africa’s already overstretched healthcare budget. Methods: In this cross sectional analytical study set in three Community Health Centres (CHCs) in the Johannesburg Metropolitan Health District, 418 diabetic patients were selected. An HbA1c test was conducted for every patient and was used to classify patients into a well controlled glycaemic group (HbA1c < 7%) or a poorly controlled group (HbA1c ≥ 7%). Differences between the two groups in terms of their risk factors for poor glycaemic control were investigated. Patient related risk factors studied included, basic demographic, treatment related, clinical, behavioural and lifestyle characteristics. Healthcare professionals and facility managers were interviewed and patient records were reviewed to describe health system challenges to providing optimal care. Univariate and multivariate logistic regression models were used to determine patient related factors influencing glycaemic control. Results: Of 394 patients with a measurable outcome (HbA1c), only 62 (15.7%) had well controlled diabetes. The mean HbA1c was similar across the three CHCs studied (p=0.464). Good glycaemic control was significantly associated with unemployment, shorter duration since diabetes diagnosis, treatment with oral medication alone and normal LDL-cholesterol levels (p<0.05). On multivariate analysis significant predictors of good glycaemic control were found to be a shorter duration since diabetes diagnosis, treatment with oral medication alone, being male, and those who were unemployed. Numerous challenges to providing optimal diabetes care were reported by health professionals including high patient to staff ratios, lack of working equipment as well as a need to improve diabetes management skills. Record review revealed that only a limited number of patients (16%) had ever had HbA1c testing. Conclusions: The majority (84.2%) of patients attending the selected facilities for diabetes care had poor glycaemic control. Management of diabetes in these CHCs is suboptimal. Patients with a shorter duration of diabetes, those who were male, Black African, unemployed and treated with oral medication alone were more likely to have good glycaemic control. Although the study concludes that patient related factors are at the forefront in terms of factors influencing glycaemic control, improved strategies in all spheres can only improve diabetes management at the CHCs.
MMed, Community Health, Faculty of Health Sciences,University of the Witwatersrand
Keywords: glycaemic control; diabetes; diabetics; influencing factors